Pengaruh Perceived of Risk, Enjoyment, Social Influence, Trust, Quality of Website, dan Online Advertisment Terhadap Perilaku Belanja Online Mahasiswa - Yulin Puspita Sari; Mega Mayasari (Pusat P2M Politeknik Negeri Batam, 2022)
The study examines the effect of perceived risk, enjoyment, social influence, trust, quality of the website, and online advertisement on students' online shopping behavior. The research sample was 104 students majoring in Business Management at the Batam State Polytechnic. The sampling technique used was purposive sampling. This research method is quantitative. Data collection techniques using a survey with a questionnaire. Analysis of research data using multiple regression. The results of this study indicate that enjoyment and trust factors significantly affect students' online shopping behavior. In contrast, the perceived risk, social influence, quality of the website, and online advertising factors have no significant effect on students' online shopping behavior.